Online shopping - Fernie, Professor John (Emerald Group Publishing, 2005)
The second issue of 2005 is a themed issue on online shopping with authors fromDenmark, the US and Taiwan. Our first contribution is from Torben Hansen fromCopenhagen Business School. His paper seeks to investigate whether consumers whohave adopted online grocery buying perceive this innovation differently from otherconsumers.